Chinese herbal medicine Qing-Dai-induced pulmonary arterial hypertension in a patient with ulcerative colitis: A case report and experimental investigation - Kazuki Sato; Hiroshi Ohira; Takahiro Horinouchi; Toshitaka Nakaya; Yuichi Mazaki; Ayako Sugimoto; Taku Watanabe; Ichizo Tsujino; Masaharu Nishimura (Respiratory Medicine Case Reports, 2019)
A recent case report described a case of pulmonary arterial hypertension (PAH) associated with use of the Chinese herbal medicine Qing-Dai; however, the clinical course and possible mechanisms have not been characterized. We present the case of a man with ulcerative colitis who was diagnosed with idiopathic PAH. After initiating oral beraprost therapy, the patient showed significant hemodynamic improvements and an unusual course of clinical recovery. In 2016, the Japanese Ministry of Health, Labour, and Welfare issued a warning regarding the possible side effects of Qing-Dai. We learned that our patient had been taking self-purchased Qing-Dai for 2 years. Therefore, we performed an experimental study and determined that Qing-Dai may cause PAH through a mechanism involving nitric oxide synthase inhibition and pulmonary artery endothelial dysfunction. Keywords: Adverse event, Qing-Dai, Pulmonary arterial hypertension, Indigo